Red alternative to Malawi s green gold - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Over the past decade, sweet pepper has been promoted widely in Malawi in an attempt to diversify the country s agricultural production. It is a good alternative to tobacco, the country s green gold and main foreign exchange earner for years,...